1971
DOI: 10.1111/j.1432-1033.1971.tb01622.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Properties of Two Carboxylesterases from Rat‐Liver Microsomes

Abstract: The esterase activity of rat liver was mainly concentrated in the microsomal and nuclear fractions, with low activities in other fractions. On the basis of sensitivity t o certain esterase inhibitors, the microsomal esterases were considered to be of a carboxylesterase type. The esterase distribution in sonicated rough microsomes, separated by zone centrifugation, was also investigated.Solubilization of the microsomal esterases was achieved by sodium deoxycholate, trypsin and phospholipase-A treatment. Two est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
3

Year Published

1973
1973
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(28 citation statements)
references
References 34 publications
2
23
0
3
Order By: Relevance
“…This is in good agreement with the pH optima reported for other carboxylesterases [Z, 12,171. The corresponding profile for methyl butyrate, however, was dependent on the substrate concentration (Fig.5).…”
Section: Aromatic Amidessupporting
confidence: 81%
“…This is in good agreement with the pH optima reported for other carboxylesterases [Z, 12,171. The corresponding profile for methyl butyrate, however, was dependent on the substrate concentration (Fig.5).…”
Section: Aromatic Amidessupporting
confidence: 81%
“…Three replicates were conducted for each compound with the same enzyme preparations. Hydrolytic activity for pNPA was monitored for 2 min at 405 nm in 96-well, flat-bottomed, polystyrene microtiter plates (Dynex Technologies, Chantilly, VA) and analyzed on a Spectramax 200 plate reader (Molecular Devices, Sunnyvale, CA) according to the methods of Ljungquist and Augustinsson [14] as modified in Wheelock et al [15].…”
Section: Enzyme Activity Assaysmentioning
confidence: 99%
“…Comparison of substrate specificity observed in the present study for rabbit liver ES-IA with that reported in the literature for rat liver ES-10. In the literature, rat liver carboxylesterase ES-10 was referred to as follows: hydrolase PI 6.0 [5,14,28,[36][37][38]461; PI 6.1 csterase [42,43]; esterase El [4,39,41,44]; carboxylesterase RHI [34, 401; esterase el [35]; esterase I1 [45] [4,5,28,[34][35][36][37][38][39][40] [401 [4, 28, 39, 401 15, 351 [4> 281 14, 281 44, 45, 471 [4,281 [4> 281 [4,281 [4> 281 [5,451 1451 14, 14, 281 [4, 51 [41-431 [4, 5, 28, 36-38, 41 ~5,421 [34,401 ~14,401 ~5,141 [51 ~5,141 [4,5, 141 1461 1461 141 ~5,141 [4, 5, 14, 28, 36-41] logical substrates were poorly hydrolysed (Table 3). The octanoylglycerol esters were hydrolysed, but compounds such as acetylcholine, butyrylcholine and butyrylthiocholine were not hydrolysed.…”
Section: Discussionmentioning
confidence: 99%